Numerical investigation of fins effect for melting process of phase change materials - Varol, Yasin; Okcu, Mutlu (My University, 2013)
Dikdörtgen geometrili bir ortamda faz değiştiren maddelerin erime katılaşma süreci sayısal olarak incelenmiştir. Geometri içerisine yerleştirilen kanatçıkların ısı transferine etkisi araştırılmıştır.

The present study numerically explores the melting process of a phase change materials in a rectangular geometry. More specifically, it investigates flow field, thermal phenomena, detailed phase and melting process by means of numerical simulation which is using as parameter; melting temperature, latent and specific heat capability, thermal conductivity and density in solid and liquid states, are based on paraffin wax. The study is performed for melting in rectangular container of without fin and 5 fins, when the wall temperature is uniform. Transient numerical simulations are performed using the ANSYS-Fluent 12.0 commercial software. The simulation results show that the transient phase change process depends on PCM properties, thermal condition and geometrical parameters of system. It includes the paraffin wax properties, thermal difference between hot and cold wall, and number of fins in the rectangular container. Results also indicate that the presence of fins embedded in the container significantly accelerates the melting process.
Bildiri - Yayımlanmış
Bildiri - Kongre ve Sempozyum
Keywords: Faz Değiştiren Madde; Erime Katılaşma; Kanatçık